The Prevalence of Dry Eye After Cataract Surgery Among Acute Angle Closure Crisis Patients at Thammasat Hospital - Rojdamrongratana, Duangmontree; penpian, Chayanee (Asian Medical Journal and Alternative Medicine, 2023)
Introduction: Dry eye is a common condition. Patients with dry eye may have a reduced quality of life due to their discomfort, and significant visual disturbances. Dry eye can occur as a result of various factors such as increasing age, female, medication use, and surgical procedures. The definitive treatment of acute angle closure crisis is surgical intervention to prevent its recurrence. Objectives: The objective of the study was to identify the prevalence of dry eye after cataract surgery among acute angle closure crisis (AACC) patients by using Ocular Surface Disease Index (OSDI), which is a standardized instrument to diagnosis dry eye disease (DED). Methods: Prospective descriptive study. Twelve cases of AACC were diagnosed and underwent phacoemulsification at Thammasat Hospital. All participants were enrolled in this study. The dry eye related data was collected preoperatively and at 1 week, 1 month, and 3 months postoperatively. OSDI evaluation form was completed by all participants to record the type of dry eye. Results: Fifteen eyes of 12 patients, including 4 (33.33%) men and 8 (66.67%) women with the mean age of 67.4 (±6.1) years were studied. DED were found 73.33% eyes (P < .001) of patients at 1 week follow-up. 46.67% and 6.67% of the eyes were dry eye at 1 month and 3 months after surgery, respectively. Conclusions: Prevalence of DED is significant after cataract surgery among AACC patients. The clinicians should be concerned about DED after cataract surgery.